2009
DOI: 10.1111/j.1095-8339.2008.00942.x
|View full text |Cite
|
Sign up to set email alerts
|

A spectacular new species ofNepenthesL. (Nepenthaceae) pitcher plant from central Palawan, Philippines

Abstract: A new species of Nepenthes L., N. attenboroughii (Nepenthaceae), from Palawan Island in the Philippines, is described and illustrated. It is restricted to rocky, ultramafic soils that comprise the summit region of Mount Victoria, Municipality of Narra, where it occurs in isolation from other members of the genus. On the basis of the morphological features, this new taxon appears to be related to both N. mira Jebb & Cheek of Palawan and N. rajah Hook.f. of Borneo. Its substantial size places it among the larges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 8 publications
0
22
0
1
Order By: Relevance
“…However, horticulturists and enthusiasts often view the taxonomic importance of certain morphological traits differently from taxonomists and this may give rise to multiple, competing interpretations for some taxa. New discoveries are still being published on a regular basis , McPherson 2009, Robinson et al 2009), making it difficult to address the issue at present.…”
mentioning
confidence: 99%
“…However, horticulturists and enthusiasts often view the taxonomic importance of certain morphological traits differently from taxonomists and this may give rise to multiple, competing interpretations for some taxa. New discoveries are still being published on a regular basis , McPherson 2009, Robinson et al 2009), making it difficult to address the issue at present.…”
mentioning
confidence: 99%
“…dilaporkan tumbuh di tanah-tanah ultramafik di Gunung Kinabalu dan Gunung Tambuyokon, Sabah Malaysia diantaranya N. burbidgeae, N. edwardsiana, N. rajah, N. villosa (Van der Ent et al, 2015). N. ultra di Luzon Filipina (Cheek dan Jebb, 2013), dan N. attenboroughii di Filipina (Robinson et al, 2008).…”
Section: Pendahuluanunclassified
“…Diels 1906, Van Steenis 1953, Beaman et al 2001, Anfraix 2005, as well as from Leuser National Park of northern Sumatra (De Wilde & Duyfjes 2001). A recent expedition to the Philippines (see Robinson et al 2009, McPherson 2009) has revealed the presence of this new taxon from ultramafic habitats on two different mountains located on the island of Palawan. It is described here from herbarium specimens and observations made during that expedition.…”
Section: Introductionmentioning
confidence: 97%
“…The low soil nutrient content of ultramafics leads to a rather open vegetation (Nagy & Proctor 1997), providing conditions ideally suited to carnivorous plants, which are adapted to survive on poor soils through the capture of invertebrate prey for additional nutrition. Indeed, a high α-diversity of Nepenthes L. (Nepenthaceae) is confined to ultramafic soils in Malesia (Robinson et al 2009). …”
Section: Introductionmentioning
confidence: 99%